ASSOCIATION OF GLOMERULAR FILTRATION RATE AND DIABETES PARAMETERS WITH SYMPTOMATIC GERD IN THE ELDERLY POPULATION - Martin, Alfianto; Limas, Peter Ian; Santoso, Alexander Halim; Setiawan, Fiona Valencia; Khoto, Anthon Eka Prayoga; Cendi, Sylvia; Firmansyah, Yohanes (Jurnal Muara Medika dan Psikologi Klinis, 2024)
Background: Gastroesophageal reflux disease (GERD) is common in the elderly, with diabetes and impaired kidney function being potential contributing factors. Poor blood glucose control and declining glomerular filtration rate (GFR) may influence GERD symptoms through metabolic disturbances, delayed gastric emptying, and esophageal dysfunction. Purpose: This study aims to analyze the relationship between GFR, diabetes parameters, and symptomatic GERD in the elderly population to provide insights into their clinical significance. Methods: A cross-sectional study was conducted in 2024 with 93 elderly residents of Bina Bhakti Nursing Home, recruited through total sampling. Symptomatic GERD was assessed using the GERD-Q questionnaire, while GFR was estimated using the CKD-EPI equation. diabetes parameters, including fasting blood glucose, HbA1c, and fasting insulin, were measured via venous blood sampling. Spearman’s correlation test was used to determine associations between these variables. Results: Fasting blood glucose significantly correlated with GERD-Q scores (r = 0.223, p = 0.031), indicating that higher glucose levels were associated with more severe GERD symptoms. However, eGFR (r = 0.034, p = 0.750), HbA1c (r = 0.106, p = 0.310), and fasting insulin (r = -0.075, p = 0.475) demonstrated weak and statistically insignificant correlations with GERD severity. Age also had no significant relationship with GERD-Q scores (r = 0.015, p = 0.884). Conclusion: Poor blood glucose control is significantly associated with GERD severity in the elderly, whereas kidney function and other diabetes parameters show weaker correlations. Optimizing glycemic control may help reduce GERD symptoms and improve overall health outcomes in the elderly population.